Pop-Up Cycleways: How a COVID-19 "Policy Window" Changed the Relationship Between Urban Planning, Transport, and Health in Sydney, Australia. Issue 2 (3rd April 2023) - Harris, Mike; McCue, Peter
Abstract: Problem, research strategy, and findings: Government agencies are increasingly interested in accelerating cycleway infrastructure to achieve co-benefits of increased physical activity, transport efficiencies, and reduced greenhouse emissions. Comprehensive evidence supports this policy direction, yet delivery of infrastructure in many cities remains slow, fragmented, and wrought with political struggle. Political forces, rather than a lack of evidence, appear to be the key challenge to implementing active transport policies. In this study we used Kingdon's multiple stream theory to examine the policy development process that led to the rapid installation of pop-up cycleways in Sydney (Australia) in response to COVID-19. Takeaway for practice: Significant disruption to regular transport services induced by the COVID-19 pandemic created a policy window where political expediency resulted in rapid implementation of active transport–friendly policy and legislative changes. The policy realignment occurred due to increased government agency collaboration and the elevation of cycling to an unprecedented level of priority within government. This study shows the value of ongoing commitment to evidence-based policy solutions to clearly identified urban challenges despite institutional barriers, the need to develop political alliances for when opportunities for policy change arise, and the need to swiftly capitalize on these policy windows when they open. This case study provides insights for cycling policy development in jurisdictions traditionally burdened by skepticism and reluctance to implement bicycle infrastructure by revealing the multivalent nature of policy adoption.